Analysis of cellulose ether hydrogels for medical device application - Hellström, Sofia; Sjölander, Linnea (My University, 2022)
Intermittent catheterisation is done with a single-use catheter, by persons that, for some medical reason, cannot urinate voluntarily. At Wellspect HealthCare intermittent catheters are produced, under the name of LoFric®. Even though the company already has put a lot of effort in reducing its carbon footprint there is a great interest in making the catheters partly or wholly biobased. The catheter is coated with a hydrogel, polyvinylpyrrolidone (PVP), a fossil-based, hydrophilic and slippery coating attached to a fossil-based polyolefin-based elastomer (POBE) catheter tube. There are a lot of biobased material replacement options. Nevertheless, there are specific and high demands on a medical product that must be met. In turn, this puts specific and high demands on a possible biobased replacement. The aim of this study was to investigate biobased polymers as candidates for the hydrogel coating and for the catheter tube, and to evaluate their properties and compare them to the coating properties of PVP and POBE. It was discovered that cellulose ethers could easily form hydrogels with citric acid and successfully coat the POBE catheter. Cellulose ethers crosslinked with citric acid have previously been used as hydrogels for medical applications, but, to the extent of our knowledge, not as coatings for intermittent catheters. Thermoplastic starch (TPS) showed potential as a future POBE replacement, but is in need of further investigation. Neither cellulosebased hydrogels or TPS catheter reached the standard of the LoFric® materials but showed great promise and potential for improvement. These biobased materials, analysed in this study, showed potential to, in future, possibly replace the fossil-based parts of the current LoFric® catheter. This might improve the sustainability of the product further. However, a conversion to a biobased material does not guarantee improvement in sustainability. A life cycle assessment should eventually be carried out.
Keywords: cellulose ether; hydrogel; medical device; materials chemistry